Development Strategy for the Merah Putih Village/Sub-district Cooperative in Ogan Komering Ulu Regency - Eko Mardiantoro; Fifian Peramata Sari; Yetty Oktarina; Indah Purnomowati (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2026)
The Indonesian economy has been built on active community participation, with cooperatives serving as key instruments for inclusive economic development. The Merah Putih Village/Sub-district Cooperative (Koperasi Desa/Kelurahan Merah Putih KDKMP) plays a strategic role as a community-based economic institution that manages local resources, accommodates community aspirations, and creates productive employment opportunities. In Ogan Komering Ulu (OKU) Regency, cooperative potential remains underutilized; official data from 2024 indicate that out of 396 registered cooperatives, 168 were inactive due to limited human resources and weak managerial systems. This study aims to analyze the development strategy of KDKMP in OKU Regency. A quantitative descriptive method was employed using SWOT analysis. The sample consisted of 10 KDKMPs with 80 respondents, including cooperative managers and members, selected through purposive sampling. The results show that KDKMP development is positioned in Quadrant I, indicating strong internal conditions and favorable external opportunities. Accordingly, the recommended strategic priority is an SO (Strength–Opportunity) strategy, emphasizing the optimization of internal strengths to capitalize on external opportunities in order to enhance cooperative performance and sustainability.